The Impact of Supportive Leadership, Gender Equity Policies, and Workplace Diversity on Women’s Career Growth - Marina, Ida Ayu Putu Anandita; Santoso, R Tri Priyono Budi; Komalasari, Yeyen; Nainggolan, Gilbert (Journal La Sociale, 2026)
This study aims to examine the impact of supportive leadership, gender equity policies, and workplace diversity on women’s career growth at Hotel Tugu Bali. The research employed a quantitative approach using a survey method, with data collected from female employees through structured questionnaires. The data were analyzed using multiple linear regression analysis supported by validity tests, reliability tests, and hypothesis testing. The results show that supportive leadership has a significant positive effect on women’s career growth, indicating that leadership practices that provide support, attention, and development opportunities encourage women to grow in their careers. Gender equity policies also have a significant positive effect, suggesting that fair promotion opportunities and equal access to training contribute to women’s career advancement. In addition, workplace diversity significantly influences women’s career growth, demonstrating that an inclusive work environment enables women to feel accepted and more confident in developing their potential. Simultaneously, supportive leadership, gender equity policies, and workplace diversity have a significant combined effect on women’s career growth, indicating that career development for women is shaped by the interaction of leadership support, equitable organizational policies, and a diverse work environment. These findings highlight the importance of creating supportive leadership practices, implementing fair gender equity policies, and fostering workplace diversity to enhance women’s career growth within the hospitality industry.